CONSTITUTIONAL COURT PROCEDURE AND CONSTITUTIONAL CONTROL IN THE FIELD OF LUSTRATION - Shcherbanyuk, Oksana (Constitutional and legal academic studies, 2021)
The article considers the constitutional court procedure and constitutional control in the field of lustration. These issues are considered through the prism of the rule of law, its understanding by the Constitutional Court of Ukraine in its practice. It is emphasized that the application of the principle of publicity and the requirements of increased publicity is due to the importance of cases heard by constitutional courts, as well as the results of judicial activity. Along with this, the issue of long-term consideration by the Constitutional Court of Ukraine of the law determining lustration is analyzed in detail. The study is updated by the fact that the European Court of Human Rights on the complaints of citizens of Ukraine found a violation of the right of the lustrated to a fair trial due to excessive time of national trials for their release. It is concluded that the Law on Lustration should serve its most important function in establishing the rule of law in the country. In legal science there is a situation when the views of scholars on the essence of judicial procedure are contradictory, which gives rise to different understandings of this legal phenomenon by representatives of different scientific schools. For a long time, the problem of judicial procedure was inextricably linked with the consideration of the category of the process, the essential idea of which significantly influenced the understanding of the limits of the procedure in law. The constitutional Court as the only organ of the constitutional-judicial control may be seen as a special (organized on a state basis), the carrier of the intellectual potential of theories of constitutional law.
Keywords: constitutional court procedure; Rule of Law; constitutional control; lustration; the right to a fair trial; Ukraine; ECtHR